2017
DOI: 10.1371/journal.pone.0170857
|View full text |Cite
|
Sign up to set email alerts
|

A Low Peripheral Blood CD4/CD8 Ratio Is Associated with Pulmonary Emphysema in HIV

Abstract: ObjectivesThe prevalence of emphysema is higher among HIV-infected (HIV+) individuals compared to HIV-uninfected persons. While greater tobacco use contributes, HIV-related effects on immunity likely confer additional risk. Low peripheral blood CD4+ to CD8+ T-lymphocyte (CD4/CD8) ratio may reflect chronic inflammation in HIV and may be a marker of chronic lung disease in this population. Therefore, we sought to determine whether the CD4/CD8 ratio was associated with chronic obstructive pulmonary disease (COPD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 41 publications
(40 reference statements)
0
52
1
1
Order By: Relevance
“…The median VACS Index was 29 in PLWH compared to [18][19][20][21][22][23][24][25][26][27] in the uninfected (p<0.001). There was a trend towards higher pack years of smoking in PLWH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median VACS Index was 29 in PLWH compared to [18][19][20][21][22][23][24][25][26][27] in the uninfected (p<0.001). There was a trend towards higher pack years of smoking in PLWH.…”
Section: Resultsmentioning
confidence: 99%
“…[50] PLWH may also experience an accelerated decline in pulmonary function. [51][52][53] We have previously shown that emphysema is associated with increased immune activation and inflammation, [25,54] and increased functional limitation in PLWH. [26] Our study adds to this literature by establishing that multiple markers of COPD and the emphysema subtype are associated with increased mortality among PLWH.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[16, 23] Scans underwent a clinical read by an onsite radiologist, abstracted by a study investigator blinded to patient information to determine nodule presence and characteristics. Nodules were considered positive if they were ≥4mm and non-calcified (hereafter referred to as NCN), per NLST criteria.…”
Section: Methodsmentioning
confidence: 99%